Improving Reading Skills Using Language Learning Strategies (LLS) - Nur Yasmin Khairani Zakaria; Nora Ezzati Azmi; Norfarizah Adira Abd Hadi (Journal of Counseling and Educational Technology, 2019)
Language learning strategies are regarded as one of the most classic and conventional learning methods to be employed by language learners. In language learning, reading is regarded as one of the most resourceful method to be employed by language learners to improve their productive skills namely writing and speaking. However, little attention has been given to the aforementioned strategies to be as a mean to improve language proficiency in general. The study aims to discover language learners’ most preferred strategies to be employed in improving their reading skills in general. Distribution of questionnaires was conducted to 37 secondary school students participated in this study.  Results revealed that cognitive and planning strategies are the most preferred strategies by the students as the students were given more time and flexibility in planning their own reading. Further investigation is suggested to be conducted to a different context such as in tertiary institution.